Study on the spatiotemporal variation and driving factors of soil erosion based on sampling method in the loess hilly area of western Henan Province, China - Zhijia Gu; Keke Ji; Gaohan Xu; Ao Li; Yi Shen; Chong Yao (PLoS ONE, 2025)
The loess hilly area of western Henan Province is one of the most serious areas of soil erosion due to rugged terrain, steep slopes and weak soil resistance ability. The prevention and control of soil erosion needs to know the rate, area and distribution of soil erosion in the region, so as to accurately plan and place the corresponding soil and water conservation measures. However, the study of temporal and spatial pattern, evolution and driving force of soil erosion in this region are far more enough. Therefore, this study conducted a quantitative evaluation of soil erosion in 2011 and 2022 in the loess hilly area of western Henan Province through sampling method and field investigation based on the Chinese Soil Loss Equation (CSLE). The spatial and temporal variation of soil erosion and the driving forces of soil erosion evolution were analyzed by using geographic detector method to reveal the key driving factors affecting soil erosion. The results showed that soil erosion in the loess hilly area of western Henan showed a “double decline” (decline of soil erosion rate and soil erosion area) trend in 2022. Compared with 2011, the average soil erosion rate of the investigation units was reduced by 25.5%, and the percentage of soil erosion area was reduced by 34.0%. In 2011, the areas with high soil erosion rates were mainly distributed in the southeast of Yiyang County, the southwest of Yichuan County, the north of Song County and the southeast of Luoning County. The distribution of high value areas was scattered, mainly in the west of Shangjie District, Xingyang City and Jiyuan City. Soil erosion mainly existed in forest land and cultivated land, followed by construction land, orchard land and grassland. High soil erosion rates were distributed in the area above 25° slope, and large percentage of soil erosion area was distributed at the slope range below 6° slope. The number and density of all land patches, except orchard land, increased significantly from 2011 to 2022. The results of geographical detector analysis indicated that population was the main factor affecting the change of percentage of soil erosion area. Shannon Diversity Index, GDP, and CONTAG were identified as the key factors influencing the distribution and variation of soil erosion rates.